A new species group in Edessa Fabricius, 1803 (Heteroptera: Pentatomidae: Edessinae) - Da Silva, Valéria Juliete; Fernandes, José Antônio Marin (Zootaxa, 2012)
The caldaria group of Edessa is proposed to include four species: Edessa caldaria Distant, 1890, Edessa pantherina Bergroth,1891, Edessa rufomaculata sp. nov. and Edessa costaricensis sp. nov. Diagnoses, line drawings of the metasternal process,male and female external genitalia, digital habitus photographs and distributional maps are provided. This group can be identi-fied by rounded to ovate body shape, pattern of maculae on connexivum and stripes on ventral surface. The following syn-onyms are proposed: Edessa pacifica Breddin, 1903 = Edessa pantherina Bergroth, 1891. The lectotype of Edessa caldaria is designated.